5m-23=-28+6m

Simple and best practice solution for 5m-23=-28+6m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m-23=-28+6m equation:


Simplifying
5m + -23 = -28 + 6m

Reorder the terms:
-23 + 5m = -28 + 6m

Solving
-23 + 5m = -28 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
-23 + 5m + -6m = -28 + 6m + -6m

Combine like terms: 5m + -6m = -1m
-23 + -1m = -28 + 6m + -6m

Combine like terms: 6m + -6m = 0
-23 + -1m = -28 + 0
-23 + -1m = -28

Add '23' to each side of the equation.
-23 + 23 + -1m = -28 + 23

Combine like terms: -23 + 23 = 0
0 + -1m = -28 + 23
-1m = -28 + 23

Combine like terms: -28 + 23 = -5
-1m = -5

Divide each side by '-1'.
m = 5

Simplifying
m = 5

See similar equations:

| 4(5-a)+2(3a+1)= | | .33(x+3)+.16(x-6)=x+3 | | ln(5x-3)=2 | | 138*3d= | | 9y+5y+y= | | W^2+5w-50=0 | | 4×3/4 | | 3(x-1)+3=13 | | 5x+6=5(x+7) | | 5x-25=26+2x | | 4×3/8 | | (8-3x)/(2√(4-x)) | | -10r=-40 | | 13-9x=26-16x | | 9=-(r-5)+1 | | x^2+4n+4=0 | | 6z=-117 | | 42+4y-11=12y-11-2y | | (2w-9)(w)=110 | | (5x+4)=0 | | 8x-27+5x+18=180 | | 22+3y-6=11y-9-3y | | 17+X=22.3 | | -2x+3=7x-5 | | 0=950x^5/2 | | 6x+-5=2x+3 | | (x+3)(x-2)=2x | | 3.428571429*14=x | | 1/4(x-3)=-2 | | 23000=mx+0.05 | | 5n-6n=18 | | 7(x-4)=16+32x |

Equations solver categories